Analogies between the topological insulator phase of 2D Dirac materials and the superradiant phase of atom‐field systems. Issue 4 (14th September 2020) - Calixto, Manuel; Romera, Elvira; Castaños, Octavio
Abstract: A semiclassical phase‐space perspective of band‐ and topological‐insulator regimes of 2D Dirac materials and normal‐ and superradiant phases of atom‐field interacting models is given in terms of delocalization, entropies, and quantum correlation measures. From this point of view, the low‐energy limit of tight‐binding models describing the electronic band structure of topological 2D Dirac materials such as phosphorene and silicene with tunable band gaps share similarities with Rabi‐Dicke and Jaynes‐Cummings atom‐field interaction models, respectively. In particular, the edge state of the 2D Dirac materials in the topological insulator phase exhibits a Schrödinger's cat structure similar to the ground state of two‐level atoms in a cavity interacting with a one‐mode radiation field in the superradiant phase. Delocalization seems to be a common feature of topological insulator and superradiant phases. Abstract :